Relationships between Sedentary Lifestyle and Body Mass Index in Students in Pandemic COVID-19 - Noviyati Rahardjo Putri; Iffah Indri Kusmawati; Niken Bayu Argaheni; Angesti Nugraheni; Ika Sumiyarsi Sukamto (Journal of Epidemiology and Public Health, 2023)
Background: Students during the Covid-19 pandemic were very close to a sedentary lifestyle because of online learning patterns. This results in an increase in body mass index (BMI) due to lack of physical activity and energy burnt. The aim of this research was to find out the relationship between sedentary lifestyle and body mass index of female students during the Covid-19 pandemic. Subjects dan Method: The research method uses a quantitative analytic observational design, with a cross sectional approach. The population in this study were 110 students of the Midwifery Study Program, Faculty of Medicine, Sebelas Maret University. Sampling using the Slovin formula as many as 85 respondents with a confidence level of 95%. The research dependent variable is the body mass index of female students during the Covid-19 pandemic and the independent variable is sedentary lifestyle. The data collection method is to use the BMI questionnaire and the Adolescent Sedentary Activity Questionnaire (ASAQ). Data analysis used Somer's test. Results: The results showed that 61.2% of students were included in the less sedentary lifestyle classification, while 56.5% of students had a normal body mass index. The results of bivariate analysis with Somer's correlation test obtained a p-value of 0.045 and a gamma coefficient value of 0.38. Conclusion: The conclusion is that there is a relationship between sedentary lifestyle and body mass index in undergraduate students of Applied Midwifery, Faculty of Medicine, Sebelas Maret University, Surakarta. The correlation strength is moderate. It is hoped that individuals and communities can motivate themselves to carry out physical activities such as regular sports and educational institutions can facilitate learning methods that can involve physical activity in both online and offline learning. Keywords: nutrition status, sedentary lifestyle, student Correspondence: Noviyati Rahardjo Putri. Midwifery Program, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: novirahardjo@staff.uns.ac.id. Mobile: +6285742944794.